A brief history of superconductivity - Yoksan, Suthat (Food Agricultural Sciences and Technology, 2016)
This article begins with the discovery of superconductivity by Onnes in 1911, followed by the discovery of hightemperature superconductors by Müller and Bednorz in 1986 and ends with the discovery of iron-based superconductors by Hasono’s group in 2008. The major landmarks are covered and corresponding theories are presented. Some open questions are posed and a brief discussion on what new physics can be expected in the future.